TI_GERICHTE 60.2002.314 vom 28. September 2004 , istanza di promozione dell'accusa. appropriazione semplice. furto. truffa. falsità in documenti. - TI Tribunale d'appello (2004)
istanza di promozione dell'accusa. appropriazione semplice. furto. truffa. falsità in documenti.